Deconstructing Narrative, Deconstructing the death penalty. The case of Billy Budd, Sailor. Issue 11 (2nd November 2021) - Anker, Richard
ABSTRACT: This article proposes a deconstructive reading of Billy Budd, Sailor partly by situating the narrative in the context of Derrida's late seminar on the death penalty. Arguing that the core of Melville's narrative harbours the idealistic fantasy of redeeming the finitude of speech, a finitude which is thematically dramatised in the Handsome Sailor's stutter, it demonstrates how this fantasy reaches at once its most radical achievement in the execution of the death penalty and its deconstructive limit, thus revealing the fundamental inefficacity of capital punishment.